2004
DOI: 10.1590/s0004-282x2004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin serum levels in patients with severe brain lesions and in brain-dead patients

Abstract: -Introduction: Patients with severe brain lesions (SBL) and brain-dead patients (BD) frequently present with vasopressin (AVP) secretion disorders. Objective: To evaluate AVP serum levels in SBL and BD patients. Design: Prospective, open label, observational trial. Setting: A general teaching hospital. Method:Three groups of adult subjects (age ≥ 18y) of both sexes were included in this study: control group: 29 healthy volunteers; SBL group: 17 patients with Glasgow Coma Scale (GCS) ≤8; and BD group: 11 brain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
2
9
0
7
Order By: Relevance
“…Chen et al [21] reported plasma AVP levels varying from 2.2 to 8.0 pg/mL in normovolemic patients and normotensive patients, with serum osmolarity ≤ 290 mOsm/L. In a previous study of our group [22], plasma AVP values in 29 healthy adults individuals at rest were also very low (ranging from 0.4 to 5.2 pg/mL).= In the present investigation, preoperative (T0 -basal period) mean plasma AVP levels were of 1.37±0.73 pg/mL (median=1.34 pg/mL; range=0.30 -3.1 pg/mL), thus, inside those previously described by our group [22] in healthy resting adult individuals.…”
Section: Time Course Of Vasopressin In Our Patientsmentioning
confidence: 63%
“…Chen et al [21] reported plasma AVP levels varying from 2.2 to 8.0 pg/mL in normovolemic patients and normotensive patients, with serum osmolarity ≤ 290 mOsm/L. In a previous study of our group [22], plasma AVP values in 29 healthy adults individuals at rest were also very low (ranging from 0.4 to 5.2 pg/mL).= In the present investigation, preoperative (T0 -basal period) mean plasma AVP levels were of 1.37±0.73 pg/mL (median=1.34 pg/mL; range=0.30 -3.1 pg/mL), thus, inside those previously described by our group [22] in healthy resting adult individuals.…”
Section: Time Course Of Vasopressin In Our Patientsmentioning
confidence: 63%
“…Most importantly, however, several experimental and clinical studies already demonstrated that vasopressin is involved in brain edema formation. Elevated vasopressin serum levels were found in patients suffering from brain edema due to brain tumors (Tenedieva et al, 1994), subarachnoidal hemorrhage (Mather et al, 1981), cerebral ischemia (Barreca et al, 2001), or TBI (Huang et al, 2003;Cintra et al, 2004). Although ICV or intravenous application of arginine vasopressin in experimental animals does not cause swelling of normal brain (Vajda et al, 2001), it increases brain edema formation following pathological conditions, for example, cortical cold lesion (Reeder et al, 1986) or cerebral ischemia (Liu et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that patients with traumatic brain injury (TBI), subarachnoid hemorrhage, or cerebral ischemia have increased AVP levels in plasma and cerebrospinal fluid (Mather et al, 1981;Joynt et al, 1981;Cintra et al, 2004;Xu et al, 2007). Similarly, studies in rats showed an increased expression of V 1 receptor levels after experimental TBI (Szmydynger-Chodobska et al, 2004;Pascale et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Barreca and colleagues reported elevated serum AVP levels that were independent of osmo-and baro-mechanisms in post-ischemic human conditions. 41 In addition, elevated AVP levels in the cerebral spinal fluid (CSF) were found specifically in neurological disorders that have increased intracranial pressure.…”
Section: Animal Modelmentioning
confidence: 99%